Paisagens negras: arqueologia da escravidão nas Charqueadas de Pelotas/RS - Rosa, Estefânia Jaékel da (2012)
This paper presents an archaeological study of slavery in Pelotas Charlton in the nineteenth century in order to understand the dynamics of their operation and performance of labor-slave labor in these establishments. These issues were addressed by analyzing five charqueadas preserved in the stream Pelotas coast and a number of buildings that were part of a estanceiro-charqueador complex located on the banks of the old bed of the stream Santa Barbara.